Hybrid feedback active noise control headset based on binaural signal utilization. (November 2022) - Patel, Vinal; Bhattacharjee, Sankha Subhra; Cheer, Jordan; George, Nithin V.
Highlights: Hybrid binaural structure for active noise control headphone system. Nearest Kronecker product decomposition is introduced to improve noise cancellation performance. Improved noise cancellation over other FBANC schemes for headphone system. Abstract: A standard feedback active noise control (FBANC) headset utilizes the estimate of a primary disturbance at the left-ear (right-ear) error microphone to control noise only at the left (right) ear-cup, i.e., each ear's controller works independently. In contrast to the FBANC headset, in this paper, a binaural hybrid feedback active noise control (HFBANC) headset is designed that uses the estimate of the primary disturbances at both the left and right-ear error microphones to achieve improved noise control at both the left and right ear-cups. To further improve noise cancellation performance, the nearest Kronecker product decomposition technique is incorporated into the algorithm. The performance of the proposed HFBANC headset is compared to the standard FBANC headset under a variety of different sound field conditions. Experimental results show an improvement of 3–5 dB in the noise cancellation using the proposed algorithms, where the benefits are more prominent for noise sources originating from the side of the user (left and right).